Cooperation in Space Traffic Management : The USA vs. the EU - Martínek, Patrik; Machoň, Miloslav, 1988-; Strnad, Michal; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The thesis deals with the evolving space traffic management (STM) in the context of the increasing activity in the near-earth environment. It identifies threats stemming from the lack of an internationally recognized space traffic management regime. Lastly, it provides a comparative case study of the US and EU approaches to space traffic management in the context of a globally accepted STM regime.
Vedoucí práce: Miloslav Machoň
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses